ASPEK KELEMBAGAAN DAN KOMITMEN POLITIK PROGRAM KELUARGA BERENCANA ERA DESENTRALISASI DI KABUPATEN TEGAL - Agus Irfan (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2017)
In the midst of decentralization and regional autonomy issues, almost all sectors of the central government’s authority granted to local governments, including family planning programs (family planning). Similarly, the implementation of family planning programs in Tegal regency government. Based on qualitative research method, the family planning program is not running optimally due to changes in institutional planning and lack of political commitment from the local government Tegal regency. Family planning programs have not been considered as a matter of urgency. Lack of political commitment to produce policies that do not support the implementation of family planning programs and the impact on the lack of budgetary allocations, lack of human resources support, overlapping regional regulations, and institutions that have not been independent for family planning programs.